1995
DOI: 10.1074/jbc.270.43.25685
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synthesis and Assembly of Photosystem II Core Proteins

Abstract: The D1 reaction center protein of the membranebound photosystem II complex (PSII) has a much higher turnover rate than the other PSII proteins. Thus, the D1 protein has to be replaced while the other PSII components are not newly synthesized. In this study, this D1 protein replacement into PSII complexes was followed in two in vitro translation systems: isolated chloroplasts and a homologous run-off translation system consisting primarily of isolated thylakoids with attached ribosomes. The incorporation of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 39 publications
(57 reference statements)
7
58
0
Order By: Relevance
“…2B) either as a ratio (upper plot) or separately (lower plot). All ORFs encoding proteins that were shown previously to integrate cotranslationally into the thylakoid membrane (PsbA, PsbB, PsbC, PsbD, PsaA PsaB, and PetA) (10)(11)(12)(13)22) are represented by prominent membrane-associated peaks, validating the method. Additional peaks revealed the thylakoid-associated translation of 12 proteins that had not been assayed in prior studies: AtpF, AtpI, PetB, NdhA, NdhB, NdhC, NdhD, NdhE, NdhF, NdhG, Ycf4, and CcsA (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…2B) either as a ratio (upper plot) or separately (lower plot). All ORFs encoding proteins that were shown previously to integrate cotranslationally into the thylakoid membrane (PsbA, PsbB, PsbC, PsbD, PsaA PsaB, and PetA) (10)(11)(12)(13)22) are represented by prominent membrane-associated peaks, validating the method. Additional peaks revealed the thylakoid-associated translation of 12 proteins that had not been assayed in prior studies: AtpF, AtpI, PetB, NdhA, NdhB, NdhC, NdhD, NdhE, NdhF, NdhG, Ycf4, and CcsA (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Pioneering studies demonstrated that some chloroplast ribosomes are attached to the thylakoid membrane by the nascent peptide, implying a cotranslational integration mechanism (8,9). Several specific plastid-encoded proteins have been shown to integrate cotranslationally: the PSII subunits PsbA (also known as D1), PsbB, PsbC, and PsbD; the PSI subunits PsaA and PsaB; and the cytochrome b 6 f subunit PetA (also known as cytochrome f) (10)(11)(12)(13)(14). The insertion of PetA into the membrane requires cpSecA (12,15,16), whereas PsbA integrates independent of both the cpSecA and cpTAT systems (17).…”
mentioning
confidence: 99%
“…Newly synthesized D1 protein is reassembled into existing PSII complexes. In two recent studies it has been shown that such replacement of the D1 protein can be achieved both in isolated chloroplasts and in isolated thylakoids [4,5]. The sequence of synthesis and assembly was partially resolved by pulse-chase experiments in these in vitro systems [5].…”
Section: Introductionmentioning
confidence: 97%
“…The distribution of PSII proteins and PSII (sub)complexes in the sucrose gradient fractions was determined by several biophysical and biochemical techniques as described in [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation